NOMINA KOSMIS DALAM BAHASA JAWA - Ashari Hidayat (Adabiyyāt: Jurnal Bahasa dan Sastra, 2010)
Cosmic nouns in Javanese language are a group of nouns, which refers to astronomic and geographic notion. This research aims at describing its morphologic and syntactic characteristics. This research uses distributional and equivalent method. The data is collected from everyday use of language as well as its variety of the language, literature, and dictionary. The astronomic nouns refer to "sun", "moon", and "star". The geographic nouns refer to ‘location’ and ‘direction’. Morphologically, cosmic nouns can be in the form of simple noun or complex noun from affixation. Some can be reduplicated while others can’t. Some demonstrative and negation of Javanese language can be jointed with cosmic nouns. Syntactically, cosmic nouns can be in phrasal form. The dominant phrasal form, which emerges, has endocentric relation – having center form which is clarified by peripheral form. Based on its references, astronomic and geographic nouns are categorized into specific and general noun. The complexity of cosmic noun is bound to the number as well as distance of the referent noun. The result of this research shows that cosmic nouns have its unique characteristics compared to other nouns.